Potential effects of dynamic stretching on injury incidence of athletes: a narrative review of risk factors - Behm, D. G.; Alizadeh, S.; Daneshjoo, A.; Konrad, A. (Sports Medicine, 2023)
The use of dynamic stretching as a replacement for static stretching in the warm-up is widespread based on the reports of static stretching-induced performance impairments. While acute and chronic static stretching has been reported to reduce musculotendinous injuries, especially with explosive and change of direction actions, the influence of dynamic stretching on injury incidence lacks a similar volume of literature for acute and chronic responses. It was the objective of this narrative review to examine the acute and training effects of dynamic stretching on injury incidence and possible moderating variables such as dynamic stretching effects on range of motion, strength, balance, proprioception, muscle morphology, and psycho-physiological responses. One study demonstrated no significant difference regarding injury incidence when comparing a dynamic stretching-only group versus a combined dynamic stretching plus static stretching group. The only other study examined functional dynamic stretching training with injured dancers and reported improved ankle joint stability. However, several studies have shown that dynamic activity with some dynamic stretching exercises within a warm-up consistently demonstrates positive effects on injury incidence. Regarding moderating variables, while there is evidence that an acute bout of dynamic stretching can enhance range of motion, the acute and training effects of dynamic stretching on strength, balance, proprioception, and musculotendinous stiffness/compliance are less clear. The acute effects of dynamic stretching on thixotropic effects and psycho-physiological responses could be beneficial for injury reduction. However, the overall conflicting studies and a lack of substantial literature compared with SS effects points to a need for more extensive studies in this area.